Comparative analysis of the diet of Arctocephalus gazella (Pinnipedia), at two localities of the South Shetland Islands, with emphasis on the fish component - Descalzo,Mariana (2021)
ABSTRACT We studied the diet of non-breeding male Antarctic fur Seals Arctocephalus gazella (Peters, 1875) at two different localities of the South Shetland Islands: Stranger Point, King George Island/Isla 25 de Mayo and Duthoit Point, Nelson Island, by the analysis of 65 faecal samples collected in February 2012. Overall, Antarctic krill Euphausia superba (Dana, 1850) and fish were the main prey taxa followed by penguins and cephalopods. Myctophids were dominant among fish; Gymnoscopelus nicholsi (Gilbert, 1911) was the most important prey species at both sampling sites, followed by Electrona antarctica (Gunther, 1878) at Stranger Point and by the nototheniid Pleuragramma antarctica (Boulenger, 1902) at Duthoit Point. The relative similarity found in the dietary composition of fur seals from both locations suggest they might have been sharing common feeding areas. Our results were compared with those reported in the literature for different localities of the South Shetland Islands and the Scotia Sea region. The absence of formerly harvested demersal notothenioid species in the diet of fur seals may reflect the negative impact that commercial fisheries had on some fish populations and supports the importance of implementing long-term monitoring studies on the feeding habits of A. gazella in the area.